Sugar recovery from bakery leftovers through enzymatic hydrolysis : effect of process conditions and product characterization - Nurfatimah Mohd Thani; Siti Mazlina Mustapa Kamal; Farah Saleena Taip; Alifdalino Sulaiman; Rozita Omar (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study evaluates the process conditions, (enzyme concentration (120-1200 U/g substrate), temperature (30-60 °C), and pH (3-9)) of enzymatic hydrolysis (EH) for sugar recovery from leftover croissants (LC) and leftover doughnut (LD), and characterizing its residue and hydrolysate. The highest sugar yield recovered from LC was 574.21 ± 0.74 mg/g (840 U/g substrate, 49 °C and pH 3) and for LD was 460.53 ± 0.74 mg/g (1176 U/g substrate, 47 °C and pH 3). The highest fructose and glucose yield for LC and LD were 14.47±0.73 mg/g and 11.84±0.21 mg/g, and 13.26±0.63 mg/g and 10.34±0.11 mg/g, respectively. Morphology analysis (SEM) showed that the structure of LC and LD had changes in its starch granules that indicates hydrolysis process occurrence. The presence of monosaccharides and oligosaccharides were detected from FTIR. HMF was also detected from sugar degradation due to EH, (0.043 ± 0.0334 mg/g for LC) and (0.023 ± 0.0124 mg/g for LD).